Lost years of life adjusted for disability among nursing professionals due to COVID-19 infection in Brazil (Research, Society and Development, 2020)
Introduction: The burden of disease attributable to COVID-19 infection among health professionals at the forefront of combating the disease, hitherto unknown, must guide policies for coping with the pandemic, considering the particularities of each professional category and the regionalities. Objectives: To estimate the disease burden attributable to COVID-19 infection among nursing professionals, to estimate the Years of Life Lost due to premature mortality (YLL), to estimate the Years Lost due to Disability (YLD) and to estimate the Adjusted Years of Life for Disability (DALY) from March 20th to May 5th, 2020. Method: Ecological study. Data on mortality, morbidity and expectations by age group of nursing professionals registered at the Nursing Observatory of the Federal Council of Nursing (COFEN) at the Brazilian Institute of Geography and Statistics (IBGE) were used. The weight of the diseases was extracted from the 2017 Global Disease Burden Study (GBD), considering the lower respiratory tract infection to be moderate. The analysis considered the distribution according to professional category, sex and age group. Results: 81 deaths and 6427 professionals diagnosed with COVID-19 were analyzed. Brazilian nursing lost 562.51 DALY (95% CI 495.24 - 629.79). Of these, 88.35% were due to premature death. The rate of DALY lost per 1000 professionals standardized by age was 87.52. DALY was higher among professionals aged 31 - 40 years old (926.12). Conclusion: More than 500 DALY were lost in Brazil due to COVID-19 infection among nursing professionals, essentially due to premature mortality.